Mastery of Your Anxiety and Panic 2022
DOI: 10.1093/med-psych/9780197608678.003.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Panic Disorder and Agoraphobia

Abstract: This chapter provides an overview of the nature of panic disorder and agoraphobia. The key features of panic disorder are (1) one or more episodes of abrupt, intense fear or discomfort (i.e., a panic attack) and (2) persistent anxiety or worry about the recurrence of panic attacks, their consequences, or life changes as a result of the attacks. Individuals with panic disorder often avoid, feel hesitant about, or feel nervous in situations where they expect panic attacks or other physical symptoms to occur. Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Both the current study and that of Vanzhula et al [ 24 ] showed a significant positive effect of distraction on binge eating/purging behaviors; however, given the difference in the effect sizes, it is suggested that limited distraction from foods, rather than generalized distraction, contributes to the increase in binge eating/purging behaviors. Therefore, although several studies have argued that distraction can function as an avoidant strategy that can exacerbate levels of AEB [ 13 , 59 , 60 ], our data suggest that generalized distraction may have little effect on the severity of AEB during adolescence.…”
Section: Discussioncontrasting
confidence: 72%
“…Both the current study and that of Vanzhula et al [ 24 ] showed a significant positive effect of distraction on binge eating/purging behaviors; however, given the difference in the effect sizes, it is suggested that limited distraction from foods, rather than generalized distraction, contributes to the increase in binge eating/purging behaviors. Therefore, although several studies have argued that distraction can function as an avoidant strategy that can exacerbate levels of AEB [ 13 , 59 , 60 ], our data suggest that generalized distraction may have little effect on the severity of AEB during adolescence.…”
Section: Discussioncontrasting
confidence: 72%
“…In three studies, six-degrees of freedom tracking allowed patients to move within a small area and hold on to a physical railing which was also represented virtually (Krijn et al, 2004;Whitney, 2005;Meyerbröker et al, 2018). In some studies, difficulty could be manipulated by increasing the height and/or perceived safety of the situation (Coelho et al, 2006;Graske and Barlow, 2008;de Quervain et al, 2011).…”
Section: Specific Phobiamentioning
confidence: 99%
“…17,18 In patients with anxiety or respiratory diseases, interoceptive sensations from cardiorespiratory organs including chemosensors for blood gases, can trigger panic attacks via catastrophic misappraisal or conditional fear responses. 1721 During panic attacks, common sensations include cardiovascular, respiratory and psychological symptoms of asphyxiation, palpitations, chest pain, dyspnea, choking, nausea, dizziness, flushing, supported by objectively measured elevated heart rate and blood pressure, changes in breathing pattern, and exaggerated startle response. 22 For some patients, dyspnea (i.e., breathlessness) is useful as a physiological marker of anxiety as well as a treatment target using interoceptive interventions.…”
Section: The Role Of Interoception In Breath-based Mind-body Therapiesmentioning
confidence: 99%